Against all odds: women's motivation to become STEM entrepreneurs in Sri Lanka - Arosha Adikaram; Ruwaiha Razik (Journal of Business and Socio-Economic Development)
Purpose – This paper aims to explore the motivations behind women in a developing South Asian country – Sri Lanka – to embark on entrepreneurship in science, technology, engineering and mathematics (STEM) fields, which is a doubly masculine hegemony operating within a culturally nuanced gendered context. Design/methodology/approach – The study employs a qualitative research approach, conducting in-depth semi-structured interviews with 15 STEM women entrepreneurs, following the theoretical lenses of push and pull motivation theory and gender role theory. Findings – Although the motivations of STEM women entrepreneurs cannot be exclusively categorized as either push or pull factors, the pull factors had a greater influence on the participants in motivating them to become entrepreneurs. The primary motivators for starting businesses in STEM were: inspiration from something or someone, inner calling, the identification of business opportunities, the need for flexibility, necessity and/or desire to help society. It was often difficult to identify one dominant motivator in many instances, as many factors were interlinked to motivate women to start a business. The study also revealed that gender ideologies could stifle the participants' motivation, while the inner need to break these gender ideologies implicitly stimulated their motivation. Originality/value – The study contributes to and expands the knowledge of STEM women entrepreneurs in general and to the limited existing knowledge of STEM women entrepreneurs in developing countries specifically. The paper brings contextual novelty as Sri Lanka produces more female STEM graduates than men, which is unique compared to most other parts of the world.